Evaluation of wound healing potential, antioxidant activity, acute toxicity and gastro protective effect of 2-pentadecanone in ethanol induced gastric mucosal ulceration in rats / Sareh Kamran - Sareh , Kamran (2020)
Wound is an injury to normal tissue that can happen either externally or internally such as wound in skin tissue or stomach tissue. Compound 2-pentadecanone a ketone derivative, has been identified in some plants, and was reported to have anti-bacterial, antioxidant and anti-inflammatory activities. The aim of this study was to evaluate skin wound healing and gastro-protective potential effect of 2-pentadecanone in Sprague dawley rats. Acute toxicity assay was performed to detect safety of 2-pentadecanone. In the evaluation of skin wound healing, dorsal neck of rats were induced wounds and topically treated with 2-pentadecanone for 10 days. Meanwhile, for gastroprotective study, rats were pre-treated orally with 2-pentadecanone and gastric ulcer was induced by absolute ethanol. Next, skin tissues and stomach tissues were collected for tissue homogenate preparation. Analysis of anti-oxidant effect of 2-pentadecanone in tissue homogenate (superoxide dismutase, catalase and malonialdehyde level determination), percentage of skin wound closure, percentage of stomach ulcer inhibition, macroscopic observations, histological staining (Hematoxylin and Eosin, Masson Trichrome and periodic acid schiff) and immunohistochemistry (HSP70 and BAX) were performed on skin and stomach tissues. Additionally, the level of nitric oxide was measured in stomach tissue. Anti-oxidant effect of 2-pentadecanone on both skin and stomach tissue homogenate was detected. Treatment of skin wounds and pre-treatment of stomachs with 2-pentadecanone resulted in over expression of superoxide dismutase and catalase enzymes and reduction in malonialdehyde level in tissue homogenate in both samples. In studies, percentage of wound closure, percentage of stomach ulcer inhibition, macroscopic and histological analysis of wounded skin and stomach tissues revealed a positive result of 2-pentadecone applications. Immunohistochemistry assay showed up-regulation of Hsp70 and down-regulation of Bax protein in skin granulation tissue of treated groups with 2-pentadecanone and stomach tissues of pre-treated rats with this compound. The present results suggested that 2-pentadecanone has promising wound healing and gastro-protective potential effect.